2023
DOI: 10.1007/978-3-031-28486-1_13
|View full text |Cite|
|
Sign up to set email alerts
|

An In-Depth Measurement Analysis of 5G mmWave PHY Latency and Its Impact on End-to-End Delay

Abstract: Fifth Generation (5G) mobile networks mark a significant shift from previous generations of networks. By introducing a flexible design, 5G networks support highly diverse application requirements. Currently, the landscape of previous measurement studies does not shed light on 5G network configuration and the inherent implications to application performance. In this paper, we precisely fill this gap and report our in-depth multi-country measurement study on 5G deployed at mid-bands. This is the common playgroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…The correlation between the throughput, angle, distance to the antenna, and performance variation when moving in a vehicle was clarified. Fezeu et al [15] analyzed the performance of mmWave radio in the physical layer corresponding to the end-to-end latency for downlink and uplink transmissions. They observed that increased delays in the physical layer can lead to congestion and jitter on the application layer.…”
Section: Research On the Performance Of 5g Cellular Networkmentioning
confidence: 99%
“…The correlation between the throughput, angle, distance to the antenna, and performance variation when moving in a vehicle was clarified. Fezeu et al [15] analyzed the performance of mmWave radio in the physical layer corresponding to the end-to-end latency for downlink and uplink transmissions. They observed that increased delays in the physical layer can lead to congestion and jitter on the application layer.…”
Section: Research On the Performance Of 5g Cellular Networkmentioning
confidence: 99%